Pembuatan Abon Ikan Kuniran (Upeneus Sulphureus) sebagai Makanan Tambahan Balita Gizi Kurang Berbasis Pangan Lokal - Setyaningsih, Sulasyi; Ratnasari, Diah (Universitas Muhadi Setiabudi, 2024)
The purpose of this research is to analyze the organoleptic test and determine the nutritional content of fat, carbohydrates, and protein in kuniran fish shreddeds for consumption by malnourished toddlers. This study was conducted in Brebes Regency in September 2020. The research design used was an experimental design. This study used a Completely Randomized Design (CRD) with 1 factor (spice concentration), 3 types of formulations, and 3 repetitions. The organoleptic test data were analyzed descriptively and statistically using variance analysis (ANOVA), followed by Duncan's multiple range test. The results showed that all hedonic test variables did not indicate differences in the preference levels of color, aroma, taste, and texture of kuniran fish floss for each formula (P < 0.05). Based on the hedonic test results, the most preferred kuniran fish floss by the panelists was the F1 formula with the highest spice concentration. The hedonic quality test results for the F1 kuniran fish floss were slightly brown (3.44), slightly coarse (3.16), slightly strong fish aroma (3.32), and slightly strong fish taste (3.16).